Quantification and prediction of human fetal (-)-Δ9-tetrahydrocannabinol/(±)-11-OH-Δ9-tetrahydrocannabinol exposure during pregnancy to inform fetal cannabis toxicity - Aditya R. Kumar; Lyndsey S. Benson; Erica M. Wymore; Jocelyn E. Phipers; Jennifer C. Dempsey; Lucinda A. Cort; Jashvant D. Unadkat (Nature Communications)
Abstract Prenatal cannabis use is associated with neurodevelopmental deficits, likely due to exposure to the psychoactive cannabinoid, (-)-Δ9-tetrahydrocannabinol, and its active metabolite, (±)-11-OH-Δ9-tetrahydrocannabinol. To determine causality, preclinical studies mimicking human fetal cannabinoid exposure must be conducted. Here we show cannabinoid concentrations across gestation in maternal plasma and paired fetal tissues in trimester 1 and 2 and maternal plasma and fetal umbilical venous plasma in trimester 3. The mean ± SD trimester 1 and 2 (-)-Δ9-tetrahydrocannabinol fetal brain/maternal plasma is 0.50 ± 0.18 (n = 3), 0.45 ± 0.28 (n = 14), respectively; trimester 3 (-)-Δ9-tetrahydrocannabinol umbilical venous plasma/maternal plasma is 0.35 ± 0.13 (n = 18). To predict fetal cannabinoid exposure at different prenatal cannabis doses (oral or inhaled), we used a verified maternal-fetal physiologically based pharmacokinetic model. At an inhalational and oral dose of 10 mg (-)-Δ9-tetrahydrocannabinol, the model-predicted average fetal brain steady-state (-)-Δ9-tetrahydrocannabinol/(±)-11-OH-Δ9-tetrahydrocannabinol concentrations, at gestational week 15, are 3.7/7.0 nM and 0.73/8.9 nM, respectively. Our maternal-fetal physiologically based pharmacokinetic model can guide future studies to inform risks associated with prenatal cannabis use.